2020
DOI: 10.1002/ajmg.a.61956
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic features in MECP2 duplication syndrome: Effects of age

Abstract: Background: MECP2 Duplication syndrome (MDS) is a rare X-linked genomic disorder that is caused by interstitial chromosomal duplications at Xq28 encompassing the MECP2 gene. Although phenotypic features in MDS have been described, there is a limited understanding of the range of severity of these features, and how they evolve with age. Methods:The cross-sectional results of N = 69 participants (ages 6 months-33 years) enrolled in a natural history study of MDS are presented. Clinical severity was assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Constipation is common in autism 21,22 and other neurodevelopmental disorders 23–25 including RTT 15 . The frequency of constipation previously reported for MDS ranged from 32% to 81% 2,7,8,10,26 . In the present study, at least three‐fourths of MDS individuals had difficulty pushing out stool and passed large, hard stool and 80% of MDS individuals required laxatives to have a bowel movement.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Constipation is common in autism 21,22 and other neurodevelopmental disorders 23–25 including RTT 15 . The frequency of constipation previously reported for MDS ranged from 32% to 81% 2,7,8,10,26 . In the present study, at least three‐fourths of MDS individuals had difficulty pushing out stool and passed large, hard stool and 80% of MDS individuals required laxatives to have a bowel movement.…”
Section: Discussionsupporting
confidence: 43%
“…15 The frequency of constipation previously reported for MDS ranged from 32% to 81%. 2,7,8,10,26 In the present study, at least three-fourths of MDS individuals had difficulty pushing out stool and passed large, hard stool and 80% of The mechanism of constipation in MDS is unknown. Several studies in RTT, 7,72 as well as other neurodevelopmental disorders, 27 showed dysbiosis of the gut microbiota which may lead to an altered gut metabolome and possible neurotransmitter dysfunction.…”
Section: Constipation Is Highly Prevalent and Severe In Mdsmentioning
confidence: 54%
“…Unlike what typically happens in epileptic encephalopathies, where BS commonly represents the EEG pattern at disease onset, in our case BS pattern likely reflects a severe cerebral dysfunction secondary to advanced disease progression. As clinical worsening with older age has been suggested, studies on the natural history of epilepsy could potentially point out a progression of EEG findings [11] . Serial EEGs of 9 patients with MDS have been recently reviewed reporting an evolution from normal to abnormal activity within 1–8 years of age in half of the patients [7] .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, some clinical features, such as epilepsy, respiratory tract infections, or constipation, appear or worsen with age. As a result, Peters et al, reported that their older participants have more severe clinical symptoms, specifically regarding motor dysfunction (e.g., dystonia, scoliosis, and/or rigidity) and functional skills (e.g., motor skills, communication skills, chewing, and swallowing) [129]. A longitudinal Japanese study found a similar outcome by comparing the clinical traits of MDS boys at their first medical visit and some years later [130].…”
Section: Evolution Of the Syndrome With Agementioning
confidence: 98%
“…The core phenotype of MDS patients includes hypotonia, developmental delay (DD), mostly moderate-severe intellectual disability, autistic features, epilepsy, progressive lower extremity spasticity, poor speech development, recurrent infections, and gastrointestinal problems. Descriptions of individual cases and, specially, of large cohorts have helped us better understand the main and constant symptoms of MDS and expand its phenotype [53,102,109,113,116,119,121,123,129,130,132]. Even so, there are no publications focused on knowing the natural history of this disorder.…”
Section: Clinical Presentationsmentioning
confidence: 99%